SETTLEMENT OF NUTRITED CREDITS OF SYARI'AH FINANCING THE IJARAH MUNTAHIYA BITTAMLIC MODEL WITH LIABILITY RIGHTS IN STATE BIDDING DEBT AFFAIRS AGENCY - Muhammad Fahruddin; Vini Fitrini (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2023)
Sharia Bank is an Islamic bank that is starting to be in great demand by Indonesians, especially Muslims. Financing. In the running of the IMBT contract, bad credit problems often occur by the customer to the bank with guarantees of security rights to pay off their obligations. Usually the bank will ask the Head of the Religious Court to carry out the execution. When there is no good faith from the customer to the bank, the bank asks the Head of the Religious Court to submit a written auction request to (KPKNL) to sell auction of goods that have been executed. In this paper, the author focuses on the formulation of the problem, namely: 1. How is the IMBT model of shari'ah financing mechanism with guarantees of mortgage rights? auction implementation of the mortgage rights of Ijarah Muntahiya Bittamlik syari'ah financing with guarantees of coverage rights at BUPLN ? Bank Syariah merupakan bank Islam yang mulai banyak diminati oleh masyarakat Indonesia khususnya kaum muslim. Dalam berjalannya akad IMBT sering terjadi kendala kredit macet yang dilakukan oleh nasabah kepada bank dengan jaminan hak tanggungan untuk melunasi kewajibannya. Biasanya bank akan meminta kepada Ketua Pengadilan Agama untuk dilakanakannya eksekusi. Ketika tidak ada itikad baik dari nasabah kepada bank, bank memohon Ketua Pengadilan Agama untuk mengajukan permohonan lelang secara tertulis kepada (KPKNL) untuk mejual lelang barang-barang yang telah di sita eksekusi. Dalam penulisan ini, penulis menitikberatkan kepada rumusan masalah yaitu: 1. Bagaimana mekanisme pembiayaan syari’ah model IMBT dengan jaminan hak tanggungan?, 2. Bagaimana penyelesaian kredit macet pembiayaan syari’ah IMBT di pengadilan agama dengan jaminan hak tanggungan?, 3. Bagaimana implemestasi pelelangan terhadap hak tanggungan dari pembiayaan syari’ah Ijarah Muntahiya Bittamlik dengan jaminan hak tangungan di BUPLN?